Space Vector Modulation Based Direct Matrix Converter for Stand-Alone system - Chandra Sekhar Ajin Sekhar; Ravi Hemantha Kumar; Vijaya Raghavan Raghavendra Rajan; Murugesan Sasikumar (Institute of Advanced Engineering and Science, 2014)
In this paper Permanent Magnet Synchronous Generator (PMSG) is used for wind power generation in standalone system due to their feature of high efficiency and low maintenance cost, which was fed with smart direct matrix converter for direct AC-AC conversion, It provides sinusoidal output waveforms with minimal higher order harmonics and no sub harmonics and also it eliminate the usage of dc-link and other passive elements. Space vector modulation (SVM) controlled technique is used for matrix converter switching which can eliminate the switching loses by selected switching states.Proposed work are often seen as a future concept for variable speed drives technology.The proposed model for RL load was analysed and verified by varying the resistor and inductance value and analysed using MATLAB simulation.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.5104